THE SITUATION OF INTERNATIONAL RELATIONS BEFORE THE BEGINNING OF THE BALKAN WARS 1912- 1913 AS A PRECURSOR OF THE FIRST WORLD WAR - Bregu, Edit Kane (European Scientific Journal, ESJ, 2014)
After the European Concert of 1815, “Old” Europe, characterized from ongoing wars for power, experienced the longest pediod of peace it ever had. In 40 years there were no war between the Great Powers. After the war at Crime in 1854, there was no general war for another 60 years. This was due to a strong equilibrium, wich proposed the existence of France, Germany, Austro-Hungary and Russia as main elements, having the support of England wich had the naval fleet superiority. The Balkan Wars of the 1912-1913 are the most important event in the history of the Balkan people and beyond. They are composed of a series sharp and bloody conflicts that swept Eastern Europe in the recent years. If we talk about the origins of the war, we must emphasize that the situation of the Balkan wars at the time and especially the situation that followed, was very alike to the conditions that existed before the Turks came to Europe. At that time, both during and after the Balkan Wars, the Christian states constantly fought against each other for hegemony in the peninsula. For the more serious and real judgment we should also see the impact and performance of the situations and events in the Balkans, with the new changes in the geopolitics of the European continent, at least since the early nineteenth century and the credit for this goes to the European Concert (1815).